The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/s0102-053620180114
|View full text |Cite
|
Sign up to set email alerts
|

Morphoagronomic characteristics display high genetic diversity in Murupi chili pepper landraces

Abstract: Murupi chili pepper is a hot Amazonian pepper that has been used as flavoring in the region, yet its diversity is unknown. This paper aims to assess the diversity in 20 landraces from Peruvian, Colombian, and Brazilian Amazon. The experiment was installed in Manaus-AM, using a randomized complete block design with three replicates and five plants per plot. Analyses of variance showed significant differences for all nine descriptors. Fruit yield showed, in average, to be 208.08 fruits per plant, tantamount to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(4 reference statements)
2
4
0
Order By: Relevance
“…The later accession, commonly known as "pimenta-de-cheiro" (C. chinense), showed the higher average, with176 cm. Similar results were obtained by Araújo et al (2018) that analyzed 20 genotypes of peppers belonging to Peruvian, Colombian, and Brazilian Amazon Forest, and observed C. chinense with a greater high of 100.12 cm. The accessions BAGC 110, 177, and 209 were clustered for NDF and NDM, presenting later reproductive cycle and later days to fruiting (Table 3).…”
Section: Resultssupporting
confidence: 86%
“…The later accession, commonly known as "pimenta-de-cheiro" (C. chinense), showed the higher average, with176 cm. Similar results were obtained by Araújo et al (2018) that analyzed 20 genotypes of peppers belonging to Peruvian, Colombian, and Brazilian Amazon Forest, and observed C. chinense with a greater high of 100.12 cm. The accessions BAGC 110, 177, and 209 were clustered for NDF and NDM, presenting later reproductive cycle and later days to fruiting (Table 3).…”
Section: Resultssupporting
confidence: 86%
“…Nitrogen fertilization positively affected plant growth without altering antioxidant content. Regarding the growth of pepper genotypes, in general, the results of the present study are similar to those reported by Araújo et al (2018) and Ferraz et al (2016). In pepper plants, plant height and stem diameter are strongly influenced by nitrogen fertilization (Oliveira et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In C. chinense, fruit yield is similar, ranging from 280-570 g per plant (Domenico et al, 2012). In traditional varieties of C. chinense, fruit yield was, on average, 380 g. However, these varieties presented great variation for fruit yield, ranging between 70-1920 g per plant (Araújo et al, 2018), indicating large amplitude for this characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Such complex studies lead to precise recommendations through the programming of hybridization to create variability (Tirupathamma et al, 2018). Characterization of the value of a genotype must be done by means of some descriptors, among which the most used are the number of fruits per plant and their weight (Araujo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%